A new genus and species of ambush bugs from South Africa (Hemiptera: Heteroptera: Reduviidae: Phymatinae) - Rédei, Dávid; Jindra, Zdeněk (Zootaxa, 2013)
Doesburgella gen. nov. and its type species D. dilatata sp. nov. (Hemiptera: Heteroptera: Reduviidae: Phymatinae: Macrocephalini) are described from South Africa.